The ability of inner cell mass cells to self-renew as embryonic stem cells is acquired upon epiblast specification - Boroviak, Thorsten (Nat Cell Biol, 2014)
The precise relationship of embryonic stem cells (ESC) to cells in the mouse embryo remains controversial. We present transcriptional and functional data to identify the embryonic counterpart of ESC. Marker profiling shows that ESC are distinct from early inner cell mass (ICM) and closely resemble preimplantation epiblast. A characteristic feature of mouse ESC is propagation without ERK signalling. Single-cell culture reveals that cell autonomous capacity to thrive when the ERK pathway is inhibited arises late during blastocyst development and is lost after implantation. The frequency of deriving clonal ESC lines suggests that all E4.5 epiblast cells can become ESC. We further show that ICM cells from early blastocysts can progress to ERK-independence if provided with a specific laminin substrate. These findings suggest that formation of the epiblast coincides with competence for ERK-independent self-renewal in vitro and consequent propagation as ESC lines.